112 | | $\displaystyle \sum_{\pm i, \pm j,i \ne j} \alpha_{\pm i, \pm j} T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}} = \sum_{\pm i, \pm j,i < j} \left ( \alpha_{\pm i, \pm j} + \alpha_{\pm j, \pm i} \right ) T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}} = \sum_{\pm i, \pm j,i < j} \alpha*_{\pm i, \pm j}T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}}$ |
| 112 | $\displaystyle \sum_{\pm i, \pm j,i \ne j} \alpha_{\pm i, \pm j} T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}} = \sum_{\pm i, \pm j,i < j} \left ( \alpha_{\pm i, \pm j} + \alpha_{\pm j, \pm i} \right ) T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}} $ |
| 113 | $= \sum_{\pm i, \pm j,i < j} \alpha*_{\pm i, \pm j}T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}}$ |